Where are we now? And where are we going? A report from the Accelerate Brain Cancer Cure (ABC2) Low-grade Glioma Research Workshop. Issue 2 (4th December 2013) - Huse, Jason T.; Wallace, Max; Aldape, Kenneth D.; Berger, Mitchel S.; Bettegowda, Chetan; Brat, Daniel J.; Cahill, Daniel P.; Cloughesy, Timothy; Haas-Kogan, Daphne A.; Marra, Marco; Miller, C. Ryan; Nelson, Sarah J.; et al.
Abstract: Diffuse gliomas consist of both low- and high-grade varieties, each with distinct morphological and biological features. The often extended periods of relative indolence exhibited by low-grade gliomas (LGG; WHO grade II) differ sharply from the aggressive, rapidly fatal clinical course of primary glioblastoma (GBM; WHO grade IV). Nevertheless, until recently, the molecular foundations underlying this stark biological contrast between glioma variants remained largely unknown. The discoveries of distinctive and highly recurrent genomic and epigenomic abnormalities in LGG have both informed a more accurate classification scheme and pointed to viable avenues for therapeutic development. As such, the field of neuro-oncology now seems poised to capitalize on these gains to achieve significant benefit for LGG patients. This report will briefly recount the proceedings of a workshop held in January 2013 and hosted by Accelerate Brain Cancer Cure (ABC 2 ) on the subject of LGG. While much of the meeting covered recent insights into LGG biology, its focus remained on how best to advance the clinical management, whether by improved preclinical modeling, more effective targeted therapeutics and clinical trial design, or innovative imaging technology.